On plotting the scheme of fracture-mega-block tectonics of the Ukrainian Shield in a scale 1 : 500 000 - Gintov, O.B.; Yentin, V.A.; Mychak, S.V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2017)
The main principles have been proposed for discussion on composing the Scheme of fracrture-mega-block tectonics of the Ukrainian Shield in a scale 1 : 500 000 supported by a decision of Inter-departmental tectonic committee of Ukraine as a basis for plotting the Tectonic map of the Ukrainian Shield in the mentioned scale. The existing maps and schemes of the blocky subdivision of the Ukrainian Shield considerably differ from each other especially because the fact that the unified principles of blocky and especially mega-blocky subdivision for the whole shield were not yet formulated then and the criteria for subdivision and mapping of inter-mega-block fracture zones were not supported. Such criteria are being considered in this work, and examples of schemes of fracture-block tectonics of three sheets in a scale 1 : 200 000 composed on their base have been given. It is proved that the Scheme of fracture-mega-block structure of the Ukrainian Shield must reflect the present-day blocky subdivision of the earth crust formed at the border of Early and Middle Proterozoic, at the very end of establishment of the granite socle of the shield. Only such mega-blocks and blocks and in the first place fault zones, which separate them, may be exactly identified and mapped that is an important condition, because the most part of deposits and ore manifestations of the shield are just related to the fracture zones. More ancient margins of mega-blocks and fault zones in the areas of Early Proterozoic tectonic-magmatic activation are hypothetical and cannot be mapped unambiguously. It has been shown that while plotting the Scheme of fracture-mega-block tectonics of the Ukrainian Shield the priority belongs to geophysical methods.